1998
DOI: 10.1128/aem.64.6.2065-2071.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Above-Optimum Growth Temperature and Cell Morphology on Thermotolerance of Listeria monocytogenes Cells Suspended in Bovine Milk

Abstract: The thermotolerances of two different cell forms of Listeria monocytogenes (serotype 4b) grown at 37 and 42.8°C in commercially pasteurized and laboratory-tyndallized whole milk (WM) were investigated. Test strains, after growth at 37 or 42.8°C, were suspended in WM at concentrations of approximately 1.5 × 108 to 3.0 × 108 cells/ml and were then heated at 56, 60, and 63°C for various exposure times. Survival was determined by enumeration on tryptone-soya-yeast extract agar andListeria selective agar, and D val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 52 publications
2
30
0
2
Order By: Relevance
“…Higher concentrations of nutrients in the bulk fluid may have favoured cells remaining in the planktonic/free-swimming form as opposed to attaching to the GAC surfaces, thus accounting for this latter result. Furthermore, previous studies have suggested that environmental stresses may result in altered cell shapes and surface roughness (Rowan and Anderson 1998;Rowan et al 2000;To et al 2002) and that high C : N ratios may indicate inadequate N supplies (Lin and Lay 2004). Thus, the altered cell shapes observed in scanning electron micrographs of attached populations at higher C : N ratios may be due to stressed cell populations.…”
Section: Discussionmentioning
confidence: 93%
“…Higher concentrations of nutrients in the bulk fluid may have favoured cells remaining in the planktonic/free-swimming form as opposed to attaching to the GAC surfaces, thus accounting for this latter result. Furthermore, previous studies have suggested that environmental stresses may result in altered cell shapes and surface roughness (Rowan and Anderson 1998;Rowan et al 2000;To et al 2002) and that high C : N ratios may indicate inadequate N supplies (Lin and Lay 2004). Thus, the altered cell shapes observed in scanning electron micrographs of attached populations at higher C : N ratios may be due to stressed cell populations.…”
Section: Discussionmentioning
confidence: 93%
“…The CAMP test was performed using standard procedures by streaking out bacteria perpendicular to Staphylococcus aureus on 5% sheep blood agar plates and observing zones of augmented haemolysis, as described elsewhere (Bubert et al 1997). Characteristic blue-green sheen from colonies by obliquely transmitted light and tumbling motility of Listeria cells were determined as described elsewhere (Rowan and Anderson 1998). The commercial biochemical API Listeria test (bioMerieux, Marcy l'Etoile, France) was used according to the manufactures instructions.…”
Section: Biochemical and Physiological Methodsmentioning
confidence: 99%
“…L. monocytogenes RIII, another rough mutant derived from a smooth strain of serovar 1/2a, was obtained from J. Potel (Institute for Medical Microbiology, Medical Academy, Hannover, Germany). The rough variants SURI and SURII were derived from parent S1 and S2 strains, respectively, under conditions of heat stress (Rowan and Anderson 1998). Stored bacteria were kept at À70 C in phosphate-buffered saline (PBS) with 20% glycerol (v/v) until used.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…The BCSA enumerated data is also observed to be consistently lower than that of the TSYEA data for treatments of 1000 pulses and more. This difference in recovery is possibly due to the added stress of dyes and antibiotics in the selective plating medium (Rowan and Anderson 1998;Rowan 1999).…”
Section: Resultsmentioning
confidence: 99%